2021
DOI: 10.1186/s12199-020-00928-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of alcohol consumption and marijuana use among young adults in the Republic of Palau

Abstract: Background This study aimed to describe the status of alcohol consumption and drug use among young adults as well as their determinants. Methods We conducted a cross-sectional study of 356 young adults (aged 18 to 24 years) living in Palau in 2013. The prevalence of self-reported alcohol and marijuana usage were compared within and between sexes, age groups, ethnicities, and education levels. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Palauan usually takes home-cooked meal or take out ‘fast-food’ become the restaurant industry developed and targeted for foreign tourists. Likewise, the proportion of people with a frequent alcohol drinking habit was very low in this study of ages 25–64 years as well as a previous report of ages 18–24 years old in Palau [ 37 ] probably because the imported alcohol beverages were expensive. Frequent vegetable intake was inversely associated with obesity and/or central obesity among women in both of total population and native Palauan.…”
Section: Discussionsupporting
confidence: 78%
“…Palauan usually takes home-cooked meal or take out ‘fast-food’ become the restaurant industry developed and targeted for foreign tourists. Likewise, the proportion of people with a frequent alcohol drinking habit was very low in this study of ages 25–64 years as well as a previous report of ages 18–24 years old in Palau [ 37 ] probably because the imported alcohol beverages were expensive. Frequent vegetable intake was inversely associated with obesity and/or central obesity among women in both of total population and native Palauan.…”
Section: Discussionsupporting
confidence: 78%
“…Research conducted in Republic of Palau had shown that the proportion of current alcohol drinking was higher in young adult aged 21-24years than in those aged 18-20yeasr, while there was no difference in marijuana use across age bands [7]. Studies had revealed that, while the cannabis consumption among adolescent boys and girls were found to be high, the prevalent and the persistent pattern of use is common among boys [8].…”
Section: Introductionmentioning
confidence: 99%